Implementasi Pemerataan Akses Pendidikan Tinggi melalui Program Beasiswa Adik Papua di Universitas Negeri Surabaya - Wabes, Putri Maria; Rahaju, Tjitjik (PANDITA: Interdisciplinary Journal of Public Affairs, 2026)
The Higher Education Affirmation Scholarship Program or ADik is a government policy aimed at expanding access to higher education for talented students from economically disadvantaged backgrounds, particularly those from 3T regions. Universitas Negeri Surabaya, as one of the host universities for ADik Papua students, plays a strategic role in promoting educational equity. This study examines the effectiveness of the ADik Scholarship implementation at Universitas Negeri Surabaya and its contribution to equitable access to higher education. The research employs a qualitative descriptive approach using Van Meter and Van Horn’s policy implementation framework, which includes policy standards and objectives, resources, characteristics of implementing agencies, implementer disposition, inter organizational communication, and economic, social, and political conditions. The findings indicate that the ADik Scholarship Program at Universitas Negeri Surabaya has effectively supported the educational financing of students from Papua in 3T regions and contributed to more inclusive higher education access. Nevertheless, challenges remain in program outreach, academic and social mentoring, and cross unit coordination in addressing socio cultural diversity. Strengthening human resources, improving integrated communication systems, and adopting culturally inclusive approaches are necessary to ensure sustainable equitable access to higher education.